Mrs. Jeffries and the mistletoe mix-up - Brightwell, Emily (Brightwell, Emily. Mrs. Jeffries mystery., 2011)
Under a bundle of mistletoe, art collector Daniel McCourt lies with his throat slit, a bloody sword next to his body. Inspector Witherspoon is determined to solve the case-preferably before the eggnog is ladled out on Christmas Eve-but of course he will require assistance from the always sharp-witted housekeeper, Mrs. Jeffries, who has a few of her own theories on why McCourt had to die by the sword.